Hepatotoxicity caused by mebendazole in a patient with Gilbert's syndrome. (18th August 2019) - Tolomeo, Manlio; Colomba, Claudia; Meli, Maria; Cascio, Antonio
Abstract: What is known and objective: Mebendazole (MBZ) is a broad‐spectrum antihelminthic agent of the benzimidazole type. Although MBZ has been reported to cause hepatic injury, case reports of severe hepatic injury are very rare. We report a case of severe hepatitis after administration of MBZ in a patient with Gilbert's syndrome affected by pinworms infestation. Case summary: Differently from other cases of hepatitis due to MBZ reported in the scientific literature, our patient received standard doses of MBZ for a short period of time. After 18 days from the start of therapy, he developed hepatomegaly, and increases in hepatic enzymes and bilirubin. Hepatic enzymes returned to normal over the following 5 weeks. What is new and conclusion: This is the first case report of important liver injury after administration of MBZ in a patient with Gilbert's syndrome. We suspected that a diminished hepatic glucuronidation of MBZ due to the reduced activity of the glucuronosyltransferase enzyme in our patient could have caused an increase in unconjugated toxic metabolites of MBZ and the consequent liver damage. Abstract : A diminished hepatic glucuronidation of mebendazole (MBZ) in Gilbert's syndrome due to the reduced UGT1A1 activity could cause the increase in the level of MBZ unconjugated toxic metabolites and the consequent induction of liver damage.